2017
DOI: 10.3758/s13423-016-1224-1
|View full text |Cite
|
Sign up to set email alerts
|

The dot-probe task to measure emotional attention: A suitable measure in comparative studies?

Abstract: For social animals, attending to and recognizing the emotional expressions of other individuals is of crucial importance for their survival and likely has a deep evolutionary origin. Gaining insight into how emotional expressions evolved as adaptations over the course of evolution can be achieved by making direct cross-species comparisons. To that extent, experimental paradigms that are suitable for investigating emotional processing across species need to be developed and evaluated. The emotional dot-probe ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 213 publications
5
110
1
Order By: Relevance
“…Recent reviews (Bantin et al, 2016;Bar-Haim et al, 2007;Frewen et al, 2008;van Rooijen et al, 2017) and empirical evidence (Price et al, 2015;Staugaard, 2009) suggested that relying on RT to study attentional bias is difficult, and different methodologies used could affect our understanding of the time course of attentional bias toward facial expressions. In addition, fMRI has been more reliable than RT in measuring attentional bias (White et al, 2016) but has very poor temporal resolution.…”
Section: Purposementioning
confidence: 99%
“…Recent reviews (Bantin et al, 2016;Bar-Haim et al, 2007;Frewen et al, 2008;van Rooijen et al, 2017) and empirical evidence (Price et al, 2015;Staugaard, 2009) suggested that relying on RT to study attentional bias is difficult, and different methodologies used could affect our understanding of the time course of attentional bias toward facial expressions. In addition, fMRI has been more reliable than RT in measuring attentional bias (White et al, 2016) but has very poor temporal resolution.…”
Section: Purposementioning
confidence: 99%
“…In their emotion recognition study, they showed that covering the face by a niqāb, hiding the lower part of the face, resulted in better fear recognition, but worse happiness recognition, compared to when the exact same parts of the face were hidden under a cap and a shawl. In their experiment, the stimuli were very briefly presented to observers who were in turn stimulated to react as fast as they could, which they did, especially when being confronted with a threat (Kret & De Gelder, 2012;see also De Valk, Wijnen, & Kret, 2015;Van Rooijen, Ploeger, & Kret, 2017).…”
mentioning
confidence: 99%
“…We used generalized linear mixed models (SPSS v20, α =.05) for the analyses, which contained a nested structure defined by trials (25) nested within sessions (21)(22)(23)(24) nested within participants (4).…”
Section: (F) Statistical Analysismentioning
confidence: 99%
“…To make inter-species comparisons of selective attention for emotions possible, the emotional dot-probe paradigm has been proven useful 22,23 . In the task, individuals have to press a central dot, followed by a short presentation of an emotional and a neutral stimulus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation